Personality and Post-traumatic Growth of Adolescents 42 Months after the Wenchuan Earthquake: A Mediated Model - An, Yuanyuan; Ding, Xu; Fu, Fang (Frontiers in Psychology, 2017)
The aim of this study was to examine the relationship of teenagers' post-traumatic growth and personality and coping style by developing a mediating model with matched data from 772 adolescents. The sample consisted of 772 adolescents (mean age=12.93,SD=1.80) from several middle schools located in the areas that were most severely affected by the earthquake. Five factor model of personality, Coping Style Scale and Post-Traumatic Growth Inventory were used to measure personality, coping and PTG of adolescents respectively. The results showed that the mean of PTG is 2.87 (SD = 0.93). Moreover, the relationship between personality and post-traumatic growth (PTG) is mediated by cognitive coping. The model’s fit indices indicated a good fit (CFI = .996, TLI =.962, NFI = .994, RMSEA = .055).Results showed that a positive cognition coping style mediated the relationship between personality and post-traumatic growth.